Regulatory effects of plant growth regulators and micro-fertilizers on recovery of fragrant rice seedlings from simulated transplanting injury - Yu, Xiangyi; Du, Xiaoqing; Liang, Xiaoying; Wang, Zixuan; Mo, Zhaowen (Frontiers in Plant Science, 2026)
Plant growth regulators (PGRs) and micro-fertilizers (MFs) and are widely used to modulate crop growth and physiological processes. This study evaluated the foliar application of specific PGRs and MFs on promoting fragrant rice seedling recovery after simulated transplanting injury. Two fragrant rice cultivars (Xiangyaxiangzhan and Yuxiangyouzhan) were grown hydroponically and exposed to an artificial treatment to simulate mechanical transplanting injury. The experiment comprised four treatment groups, foliar-sprayed of 100 mg·L-1 gibberellin (T1), 2 mg·L-1 indolebutyric acid (T2), Mg fertilizers (T3, 2 mg·L-1 Mg2+), and Zn fertilizers (T4, 2 mg·L-1 Zn2+), respectively. We established two control groups, including a non-injured (CK0) and a simulated root injury (CK) treatment, and neither received PGRs or MFs. The seedling growth morphology and physiological indices were measured and analyzed. The results demonstrated that PGR and MF application significantly altered the growth and physiological performance of rice seedlings under simulated transplanting injury, with effects varying by treatments and varieties. Compared with CK, the T1 treatment increased stem fresh weight (25.88-38.4%), stem fresh weight ratio, plant height, stem and leaf length, leaf catalase activity, stem superoxide dismutase activity, and reduced leaf malondialdehyde content. The T2 treatment induced changes in antioxidant enzyme activities, specifically leading to an enhancement in stem superoxide dismutase activity (112.15-165.64%). The T3 treatment significantly increased the root-shoot ratio (21.74-23.07%), root fresh weight ratio, root dry weight ratio, and superoxide dismutase activity in root and stem relative to CK. The T4 treatment significantly increased the root fresh weight ratio (18.32-43.03%), superoxide dismutase activity in various tissues, and peroxidase activity in root relative to CK. These findings indicate that PGRs and MFs can effectively regulate growth and antioxidant response in fragrant rice seedlings under simulated mechanical transplanting injury.